Elaboração da Entrustable Professional Activity (EPA) associada à prostatectomia radical minimamente invasiva - Loyola, Flávio Assumpção Zambelli (2022)
Introduction: to better evaluate medical students, new curriculum models emerged in the last decades, based on competences. Entrustable Professional Activities (EPAs) are units of professional practice that can be entrusted to a student once she or he has demonstrated the necessary competence to act without supervision. They can be used to enhance curriculum design and to evaluate, on a daily practice, the professionals in formation. EPAs have been used in other countries to improve medical training but hasn’t been published to Urology residency programs in Brazil. Radical prostatectomy is the gold standard treatment for localized prostate cancer and minimally invasive techniques were developed and have increasingly been done in every country, but its training has some gaps that can benefit from the Competency Based Medical Education (CBME). Objective: elaborate the Entrustable Professional Activity of minimally invasive radical prostatectomy. Methods: on the first phase of this study, the competence domains and critical competences related to the minimally invasive radical prostatectomy were developed. Then a list of initial items of the EPA was described by a panel of urology and education experts. On the second stage, these items were evaluated, through a Delphi questionnaire, by urologists, experts on the referred surgery. The questionnaire evaluated if the proposed items were complete when regards of the expected coverage of the activity, and feasible when implemented. After this, in the third phase, the final EPA, contemplating the competencies and activities necessary for its performance, was then developed. Results: after the first phase, a list of 17 EPA items was developed. 5 of these items suffered changes after the revision of the suggestions made on the 2 rounds of Delphi questionnaire and then, the final EPA was developed. Conclusion: the minimally invasive radical prostatectomy EPA, done with collaboration of education and urology experts, through a Delphi questionnaire, was properly done and contemplates the necessary activities to the evaluation of students performing this surgery, according to the specialists that participated in this study. Consensus was satisfactory in the Delphi questionnaire, which was done by specialists in the referred surgery. This instrument may benefit the training of this surgical technique and the implementation of competency based medical education in Urology as well as in robotic surgery. This EPA still requires real scenario use to be validated.